Water quality status of Buatan Lake, Rumbai Pesisir, Pekanbaru City Riau Province using pollution index - Salmaa, Nabiilah Zakiyyati; Yuliati; Fajri, N. E (Universitas Djuanda, 2024)
Buatan Lake is the only lake in Pekanbaru which was built by damming two rivers, namely the Ambang River and the Merbau River. The main purpose of building this lake is for irrigation, fishing, and tourism activities. Various activities both in the lake and around the lake will certainly cause the entry of pollutant materials into the lake. This research aims to determine the water quality status of the Rumbai Coastal Buatan Lake, Pekanbaru City. This research was carried out from July to August 2023 at the Rumbai Pesisir Buatan Lake, Pekanbaru City, Riau Province. The research method usedis a survey method. Water samples were taken three times with an interval of one month. Determining water quality status using the Pollution Index (PI) method. The parameters used to determine quality status are pH, dissolved oxygen, BOD, COD, TSS, total phosphate, total nitrogen, chlorophyll-a, and fecal coli. Water quality analysis compared to class II water quality standards (PP No.22 of 2021). The research results show that the average water quality parameters do not meet class II quality standards, namely BOD ranging from 5,6 – 5,8 mg/L, total phosphate ranging from 0,7 – 0,8 mg/L, total nitrogen ranging from 5 - 18 mg /L, and Fecal coli ranges from 10.666 – 28.333 MPN/100 mL. The average IP value of the Buatan Lake ranges from 3,3 to 4,2 with the category being lightly polluted at all observation stations. Pollution in the Rumbai Buatan Lake is caused by pressure from the enrichment of organic matter, nitrogen, and phosphate.